Meningkatkan Kemampuan Guru dalam Menetapkan Kriteria Ketercapaian Tujuan Pembelajaran (KKTP) Melalui Workshop Intern Sekolah Di SDN Karang Bayat 01 Sumber Baru - Juhairiah, Juhairiah (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study is to describe: 1) The use of internal school workshops in improving the ability of teachers to determine the learning objectives completeness criteria (KKTP) at sd negeri karang bayat 01 sumberbaru; 2) Improving the ability of teachers to set learning objectives completeness criteria (KKTP) through internal school workshops at sd negeri karang bayat 01 sumberbaru. This research is an action research. The type of action research chosen is the emancipatory type. The research design used is the kemmis model design which consists of four steps, namely: planning, implementing, observing and reflecting. The subjects of this study were teachers at sd negeri bangsri plandaan, which consisted of 10 teachers. The conclusions of this study: 1) Using internal school workshops to improve teachers' abilities in establishing learning objectives completeness criteria (KKTP) at karang bayat 01 sumberbaru elementary school, starting with initial supervision. initial supervision is carried out to identify problems that exist in determining the learning objectives achievement criteria (KKTP). The next step is to analyze the results of the supervision and then follow up by holding a school intern workshop. School intern workshops are carried out using stages that emphasize more practical knowledge so that it is easily digested by the teacher; 2) Improving the ability of teachers to determine the learning objective completeness criteria (KKTP) through internal school workshops at karang bayat 01 sumberbaru elementary school for the 1st semester of the 2022-2023 academic year from cycle i to cycle ii and achieving the minimum target set at 85%, namely in the first cycle of 63.% increased in the second cycle to 100%.